2013
DOI: 10.1177/0363546513488861
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Femoroacetabular Impingement

Abstract: This multicenter, prospective, longitudinal cohort is one of the largest FAI cohorts to date. In this cohort, FAI occurred predominantly in young, white patients with a normal BMI, and there were more female than male patients. The disease pattern of cam FAI was most common. Contemporary treatment was predominantly arthroscopic followed by surgical hip dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(83 citation statements)
references
References 39 publications
5
69
0
Order By: Relevance
“…1 Hip arthroscopy may include a combination of these procedures. 13,14 The postoperative rehabilitation program was defined as a structured rehabilitation program within the scope of a rehabilitation professional and included interventions such as manual therapy, therapeutic exercise, functional activity, sportspecific training, and modalities. Given the paucity of research identified, we included studies that reported at minimum weight-bearing restrictions, range-of-motion parameters, and return to premorbid activities.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…1 Hip arthroscopy may include a combination of these procedures. 13,14 The postoperative rehabilitation program was defined as a structured rehabilitation program within the scope of a rehabilitation professional and included interventions such as manual therapy, therapeutic exercise, functional activity, sportspecific training, and modalities. Given the paucity of research identified, we included studies that reported at minimum weight-bearing restrictions, range-of-motion parameters, and return to premorbid activities.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…6, 10 Diagnoses associated with CHJP include femoroacetabular impingement (FAI), 17 structural instability, 52 acetabular labral tears 36 and chondral lesions. 42 Often individuals with CHJP have limitations in sitting and standing, thus restricting their ability to work or complete everyday tasks.…”
Section: Introductionmentioning
confidence: 99%
“…42 Often individuals with CHJP have limitations in sitting and standing, thus restricting their ability to work or complete everyday tasks. 6, 10 Without proper management, conditions associated with CHJP may progress to hip osteoarthritis (OA). 16, 20, 41 To improve treatment of CHJP and potentially prevent or delay the onset of hip OA, there is a need to better understand the factors proposed to be associated with CHJP, in particular hip muscle performance.…”
Section: Introductionmentioning
confidence: 99%
“…28 The reported average duration of symptoms for participants with intra-articular hip pathology prior to surgery is 1 to 3 years, with 12% of patients having symptoms for more than 5 years. 5 It is possible that the long-standing duration of symptoms in the participants included in this study resulted in lack of use and subsequent deconditioning of both legs with respect to functional task performance. Finally, unilateral painful stimuli have been shown to activate the brain's cerebellum bilaterally, supplementary motor area contralaterally, and premotor area ipsilaterally.…”
mentioning
confidence: 99%